Monitoring internal load parameters during competitive synchronized swimming duet routines in elite athletes - Rodriguez-Zamora, L.; Iglesias, X.; Barrero, A.; Torres, L.; Chaverri, D.; Rodriguez, F. A. (The Journal of Strength and Conditioning Research, 2014)
The aim of the study is to compare the heart rate (HR) and rate of perceived exertion (RPE) responses as internal load indicators while performing duet routines during training and competition, both in the technical and free programs of synchronized swimming (SS). Participants were 10 SS Olympic medalists (age, 17.4 6 plus/minus 3.0 years; height, 164.0 plus/minus 6.1 cm; body mass, 52.0 plus/minus 6.4 kg; training, 36.3 plus/minus 6.2 h/wk; experience, 9.2 plus/minus 2.6 years). They were monitored while performing the same technical duet or free duet, during a training session (T) and during an official competition (C). Heart rate was continuously monitored. Rate of perceived exertion was assessed using the Borg CR10 scale. Heart rate responses during T and C were almost identical: pre-exercise mean HR (b/min) was 130.5 plus/minus 13.9 (T) and 133.6 plus/minus 7.7 (C) and quickly increased yielding mean peak values of 184.8 6 5.8 (T) and 184.8 plus/minus 6.6 (C), with interspersed bradycardic events down to 86.6 plus/minus 4 (T) and 86.3 plus/minus 5 (C). Routines were perceived as "hard" to "extremely hard" by the swimmers in both conditions, and mean RPE scores (0-10+) were equally high during C (7.9 plus/minus 1.2) and T (7.5 plus/minus 1.2) (p = 0.223). Rate of perceived exertion inversely correlated with minimum (R = 20.545; p = 0.008) and mean HR (R = 20.452; p = 0.026) and positively correlated with HRrange (R = 0.520; p = 0.011). The internal load imposed by SS duets performed during training is virtually identical to that elicited in a real competitive situation. Therefore, practicing competitive routines is suitable for developing and maintaining the cardiovascular fitness that is needed for specific conditioning in elite synchronized swimmers, with the added value of favoring exercise automaticity, interindividual coordination, and artistic expression simultaneously.